Pengendalian Hipertensi Lansia dengan Program Merona - Didi Kurniawan; Etty Rekawati; Junaiti Sahar (Jurnal Kesehatan Komunitas, 2021)
Hypertension is a silent killer is the most common health problem experienced by the elderly. Control of hypertension in the elderly is very necessary to reduce complications of hypertension. Based on these conditions, the MERONA Program was developed. The purpose is to provide an overview of the implementation of the blush program in the elderly with hypertension. The method used is a family case study and an aggregate using a family and community nursing process approach involving 10 foster families and 60 elderly people in the community selected using cluster random sampling. This program is an integration of hypertension self-management and relaxation therapy, namely music therapy, progressive muscle relaxation, and deep breathing relaxation which is carried out for 12 weeks. Evaluation of changes in behavior and family independence was carried out at the end of the 12th week using a questionnaire. Blood pressure measurements were carried out at weeks 4, 8, and 12. The results of the implementation were an increase in the behavior of the elderly, an increase in the level of family independence, and a significant decrease in systolic and diastolic blood pressure (p<0.05). The MERONA program is recommended to be applied in community health services.